A History of Scientific Archeological Research by the Imperial Archeological Commission in Samarkand - Makhmudkhon Yunusov; Olimjon Iriskulov (Researchparks Publishing, 2022)
This research will consider: The beginning of the study of Central Asia by the Imperial Archaeological Commission, includes the expedition of P.Lerch to Yangikent, Turkestan, Shymkent, Tashkent, Khojand and Uratepa in Central Asia;The first scientific study of Afrosiab; N. Veselovsky's dispatch to Central Asia in 1885 the acquisition of the first scientific data on the ancient cities of Central Asia, in particular of Samarkand, and the accumulation of a large archaeological collection;organization of a scientific-architectural expedition to Samarkand under the leadership of N.Veselovsky to complete a systematic study of architectural monuments in 1895-1896 that resulted in, the publication of the album